Clinical and biological indicators of periodontal disease in obese and non-obese adults with and without bronchial asthma. (2nd September 2022) - Ikbariyeh, Bader; Al Habashneh, Rola; Khassawneh, Basheer; Alrawashdeh, Mohammad; Elsalem, Lina; Al-Nusair, Jowan
Abstract: Objective: The present study aims to assess clinical and inflammatory parameters as indicators for periodontal disease in obese and non-obese adults with and without bronchial asthma (BA). Methods: 168 patients visiting the outpatient pulmonary clinics were divided into four groups according to BA and obesity. Obesity was defined by body mass index (BMI) and BA was diagnosed by a pulmonary consultant and being on inhaled asthma medication for at least 12 months. Participants were examined for clinical periodontal parameters and samples of gingival crevicular fluid (GCF) were taken and analyzed for the levels of 5 different inflammatory cytokines. Results: Compared with controls, obese asthmatic group had significant higher mean clinical attachment loss (CAL) (2.64 vs. 1.00, p < .001). Also, the occurrence of periodontitis was significantly higher among obese patients compared to non-obese patients ( p  = 0.003). Multivariate logistic regression model showed that age was the strongest predictor of periodontitis (aOR = 1.23). The levels of IL-1β and IL-8 were significantly higher in the non-obese asthmatic group compared to the control group ( p  < 0.05). The level of IL-6 was significantly lower in the control group compared to the other groups ( p  < 0.001). Obese patients had significantly higher concentration of hsCRP compared to non-obese patients ( p  < 0.001). There was no significant difference in the level of TNF- α between groups. Conclusions: BA and obesity combined did not seem to be associated with a significant increased risk of having periodontitis. BA and obesity are associated with increased levels of some local proinflammatory cytokines which adds to the local and systemic inflammatory burden.